An idiographic analysis of women's accounts of living with mental health conditions in Haredi Jewish communities. Issue 3 (16th March 2017) - Whiteley, Charlotte; Coyle, Adrian; Gleeson, Kate
ABSTRACT: This research examines the reported experiences of women who developed mental health conditions while they were members of Haredi Jewish communities. The research focuses on how their communities responded and how these responses affected their self-evaluations and relationships with their communities. A qualitative, idiographic approach was used. Four women were recruited through mental health charities and an online group for former community members. The women were interviewed and transcripts were subjected to interpretative phenomenological analysis. Three cross-case themes were developed: "The negative evaluation of mental health conditions in Haredi communities", "'Cloak and dagger': Secrecy and consequences of mental health problems in Haredi communities" and "Going and staying: Mental health experiences and changed relationships with Haredism/Judaism". The themes are discussed in terms of stigma and the threat posed to Haredi communities' self-understanding and self-presentation by the women voicing their mental health status within and outside the communities.